2016
DOI: 10.1007/s00402-015-2389-1
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanical influence of the deltotrapezoid fascia on horizontal and vertical acromioclavicular joint stability

Abstract: A combined lesion of the AC ligaments and the DTF resulted in a quantitatively small but significant increase in anterior rotation and a tendency in lateral translation of the clavicle in relation to the acromion. These differences were quantitatively small, so that the clinical relevance of the stabilization effect of combined AC ligaments and DTF injuries is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…A recent biomechanical study looking at the horizontal stabilizing effect of the delto-trapezial fascia (DTF) concluded that a combined lesion of the AC ligaments and DTF resulted in significantly more anterior rotation and lateral translation of the distal clavicle-however, these differences were quantitatively small and of questionable clinical relevance. 27 Possible complications might include persistent instability despite repair, loss of reduction over time, fractures of the clavicle or coracoid, endobutton slippage and neurovascular injury, though in our series we did not encounter any of these. Another potential problem would be difficulty in deploying the endobutton through the coracoid, necessitating conversion to open surgery.…”
Section: Discussionmentioning
confidence: 58%
“…A recent biomechanical study looking at the horizontal stabilizing effect of the delto-trapezial fascia (DTF) concluded that a combined lesion of the AC ligaments and DTF resulted in significantly more anterior rotation and lateral translation of the distal clavicle-however, these differences were quantitatively small and of questionable clinical relevance. 27 Possible complications might include persistent instability despite repair, loss of reduction over time, fractures of the clavicle or coracoid, endobutton slippage and neurovascular injury, though in our series we did not encounter any of these. Another potential problem would be difficulty in deploying the endobutton through the coracoid, necessitating conversion to open surgery.…”
Section: Discussionmentioning
confidence: 58%
“…Besides that, interposition of the deltotrapezial fascia in the acromioclavicular joint previous to reduction is avoided, and the risk of incomplete acromioclavicular joint reduction, particularly in grade V dislocations, is minimized ( Table 3 ). 6 The importance of this structure to AC stabilization has been described previously, and its incorrect closure is one of the most commons pitfalls in AC surgery. 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 85%
“… 6 The importance of this structure to AC stabilization has been described previously, and its incorrect closure is one of the most commons pitfalls in AC surgery. 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…16 , 27 , 28 Some hypothesize that the deltoid-trapezius complex works in synchrony to provide dynamic stability to the AC joint. 16 , 29 This equilibrium is disrupted with AC joint injuries. In fact, Lizaur et al identified that 94% of patients with AC joint separations had injury to the trapezius and/or deltoid.…”
Section: Discussionmentioning
confidence: 99%